Portuguese Ministers as Political Survivors: an empirical analysis of the first 20 Constitutional Governments - Mourão, Paulo; Martinho, Vítor Domingues (Revista de Sociologia e Política, 2020)
ABSTRACT Introduction: In this study, we evaluated the proportional risk of Portuguese Prime-Ministers and Ministers leaving office. Materials and Methods: We used consecutive days in office for each one of the 432 citizens who served in a ministerial function since 1976. Results: Exploring several divisions in this population, we concluded that individuals supported by parliamentary majorities, who served after 1986, who had higher educational credentials, and who were members of political parties exhibited lower risks of being exonerated. Conversely, being an aged person, serving during bad economic conditions, assuming several ministries simultaneously and being in charge of too-specific ministries did not ensure longer political tenures for Portuguese ministers. Discussion: Besides being the first empirical assessment of all Portuguese Ministers after 1974, this work shows how higher skills are important assets for Ministers’ tenures and how economic crises are highly stimulating for cabinets’ changes in Portugal, which corresponds to the pattern observed in most recent democratic regimens. KEYWORDS: ministerial cabinet; Portuguese constitutional governments; determinants of political survival; proportional hazard; gender.